IMPACT OF PRICE DISTORTIONS ON POTATO PRODUCTION AND CONSUMPTION IN EGYPT - Moataz Eliw; Tarek Ali; Deyi Zhou (Journal of Animal and Plant Sciences, 2019)
In order to achieve the research objectives, study period has been split into two periods; a pre-2008 crisis period (2000-2007), which is the period prior to the burst of the global financial crises, and a post-2008 crisis period (2008-2016), which is the period after the global financial crises. Chow test has been applied to measure economic impacts on the study variables. The research also applied econometric analysis by building up a Simultaneous Equations Model in order to measure interactions and overlaps between the study variables using Three Stage Least Square (3SLS), in addition to employing Partial Equilibrium Model to identify imbalances in prices and to assess the value of subsidy received by or taxes imposed on potato producers and consumers in Egypt. The results show through applying F-Chow test statistics to total production revealed no statistically significant difference between the two study periods (2000-2007 and 2008-2016), indicating no break between the two periods. However, when applied to consumption, results revealed a statistically significant difference between the two study periods, indicating a break between the two periods. Findings also revealed that average nominal protection coefficient for potato reached 0.868 during the first period, but declined to 0.842 during the second period, down by 37.83%, which means that potato producers received 87.6% and 84.2% of their product's value in world price over the two periods, respectively, indicating that the government has been imposing taxes on potato producers to subsidize domestic consumers.
Keywords: Potato crop; Chow test; Simultaneous Equations; Partial Equilibrium Model